Alternative energy for dummies - DeGunther, Rik, 1956- (Hoboken, NJ : Wiley, 2009)
From the Publisher: Get the truth about alternative energy and make it part of your life. Want to utilize cleaner, greener types of energy? This plain-English guide clearly explains the popular forms of alternative energy that you can use in your home, your car, and more. Separating myth from fact, this resource explores the current fossil fuel conundrum, the benefits of alternatives, and the energy of the future, such as hydrogen and fuel cell technology. The ABCs of alternative energy-what it is, how it works, and what the real costs are. Where we are now-learn where our current energy comes from and how much longer it will last. Take the first step-see how energy efficiency and conservation can reduce your reliance on fossil fuels. Grasp the alternatives-from nuclear power to geothermal energy to wood burning, understand the benefits that alternative energy can have on the nation. Apply alternative fuels to transportation-from biofuels to exotic propulsion to electricity, see how they are best used and how hybrid, all-electric, and fuel cell-powered vehicles work. Get a peek into the future-see what the outlook holds for each form of alternative energy discussed. Open the book and find: The pros and cons of alternative energy - A review of the current world energy economy - The problems with fossil fuels, from smog to global warming - Advantages of alternative energy - Practical results of alternatives you can use in daily life - Guidelines for investing in alternative energy vehicles - Ten ways you can bring about change right now - Insight into the future of energy production - and how you can invest in it.
Chapter 12: Digging into geothermal -- Geothermal energy basics -- Where you an find geothermal energy -- Geothermal uses -- Economics of geothermal energy -- Creating electrical power with geothermal sources -- Types of electricity-generating systems -- Things to know about geothermal power plants -- Using geothermal energy directly: Heat pumps -- What direct-source systems need -- How heat pumps work -- Types of heat pumps -- Efficiency of heat pumps -- Advantage of heat pumps -- Chapter 13: Exploring biomass -- Biomass basics -- Biomass uses -- Converting waste to energy -- Growing energy: fuel crops -- Benefits of biomass -- Looking at the future of biomass -- Large-scale biomass power -- Process of turning biomass into power -- Advantages and disadvantages of biomass power plants -- Biomass fuels -- Ethanol -- Biodiesel -- Small-scale biomass for the masses -- Getting the lowdown on biomass stoves -- Choosing a fuel -- Chapter 14: Burning wood -- What the blazes! Cleaner and more efficient ways to burn wood -- Increasing demand, improving economics -- Improving efficiencies -- Open fireplaces: Cozy and costly -- Wood-burning stoves: Efficient alternative to fireplaces -- Comparing open-and closed-vent systems -- Free-standing stoves and inserts -- Types of wood stoves -- Important points about burning wood efficiently -- Enhancing efficiency by burning the right wood -- Avoiding problems by burning the wood right -- Maintaining a wood stove -- Getting the hot air where you want it -- Stove safety guidelines -- Ensure proper installation and venting -- Bring an existing chimney up to date -- Follow manufacturer's instructions -- Chapter 15: Hydrogen fuel cell Technologies -- Basics of hydrogen technology -- Sources of hydrogen -- Extracting hydrogen -- How a fuel cell works -- Practical and pie-in-the-sky applications -- Fuel cell-powered vehicles -- Small-scale fuel cell electric power -- Hydrogen-powered home of the future -- Future of fuel cells -- Part 4: Alternatives - Transportation -- Chapter 16: Alternative transport technologies -- Turning the pages of alternative vehicle history -- Glory days of steam -- Electric-powered vehicles -- Hybrids enter the scene -- Evolving from mechanical to electrical -- Watching the rise of silicon -- Decreasing demand for mechanical controls -- Getting efficient: Same power, less weight -- Recognizing the car of the future -- Coming full circle-and back to electric -- Chapter 17: Alternative-fuel vehicles -- Natural gas in the tank -- Advantages to natural gas -- Producing natural gas -- Natural gas vehicles -- Flex fuels for vehicles -- Sources of ethanol -- Producing ethanol -- Flex fuel vehicles -- Clean diesel and biodiesel vehicles -- Diesel then and now -- Clean diesel engines -- Biodiesel -- Clean diesel and biodiesel engines -- Chapter 18: Plugging in: Electric vehicles -- Drive down memory lane -- Early electric cars, circa 1900 -- Modern electric vehicles: 1960s to today -- Basic operation of an electric vehicle -- Batteries -- Lead-acid cell battery -- Nickel-based batteries -- Practical concerns of electric cars -- Performance -- Service and maintenance -- Battery charging and replacement -- Environmental impact -- Electric car safety -- Economics of electric cars -- Chapter 19: Hybrid-electric vehicles -- History of hybrids -- Witnessing the fall of hybrid hoopla -- Watching hybrid research pick up -- First modern hybrids -- Gaining popularity -- Two key hybrid features -- Onboard ICE and battery combo -- Regenerative braking -- Hybrid technologies: Series and parallel -- Series design hybrid vehicles -- Parallel design hybrids -- Driving and owning a hybrid -- Performance and handling -- Maintenance -- Environmental impacts -- Economics of hybrids -- Buggaboos and boogeymen: Unwarranted fears -- Chapter 20: Hydrogen and fuel cell vehicles -- Fuel cell fundamentals and challenges -- Dealing with hydrogen -- High cost -- Benefits of hydrogen and fuel cells -- Hydrogen-powered vehicles -- Hydrogen fuel vehicles -- Fuel cell vehicles -- Hydrogen future -- Chapter 21: Exotic propulsion systems -- Supercapacitors -- Solar-powered vehicles -- Flywheels -- Hydraulic accumulators -- Magnetic levitation trains -- Using magnets -- Bullet trains -- Nuclear-powered ships -- Efficiency and environmental impact -- Performance and maintenance -- Safety issues -- Part 5: Part Of Tens -- Chapter 22: Ten or so myths about energy -- World is doomed to a gloomy future -- We can legislate our way out of the mess -- Electric car was deliberately killed -- Conservation and efficiency can save the world -- There's an energy shortage -- Nuclear power plants are ticking time bombs -- Electric cars will displace all others -- Anything labeled "green" is green -- Waste is bad -- Solar power can provide all our electrical needs -- Burning wood is bad for the environment -- If global warming isn't our fault, we're off the hook -- Chapter 23: Ten-plus ways to invest in an alternative-energy future -- Performing an energy audit of your home or business. -- Installing a new stove -- Using solar -- Using biofuels to power your car -- Driving a hybrid -- Installing a geothermal heating and cooling system in your home -- Driving with diesel (without the stink) -- Installing a windmill in you own backyard -- Moving into a smaller, energy-efficient home -- Living in an urban environment -- Investing in energy stocks -- Driving less -- Index.
Includes index.
0
Keywords: Renewable energy sources; Renewable energy resources